DRBAC-Healthchain (DRBAC-HC): Decentralized Role Based Access Control Framework For Achieving Security And Privacy Using Blockchain In Healthcare System (Journal of Pharmaceutical Negative Results, 2023)
With the Internet of Things' (IoTs) rapid expansion, effect, and potential, the healthcare industry is shifting to a new paradigm that permits wearable devices to collect patient medical data and use it for monitoring and diagnosis. Tamper-proof data and avoidance of the centralized record-keeping mechanism are crucial requirements in any wellness system due to its exigent and precise necessity of data requests. Along with the same, transactions’ auditability and revocation of access rights upon certain records for specific stakeholders are also a few of the other prerequisites in the medical segment. Blockchain, as a distributed ledger, offers a solution for securely storing data while providing transparency in transactions and interactions among stakeholders. Synchronous interaction among patient, doctor, pharmacy, consultant, hospital, etc. with all possible data security is another concern that could be resolved through the usage of Blockchain’s smart contracts wherein interaction among these stakeholders is permitted in a traceable and irreversible mode. The purpose of this paper is to discuss the potential use of Blockchain technology in the healthcare sector to achieve data security, transparency, and reliability without the involvement of a trusted third party. In terms of security and privacy, we survey and provide an exhaustive review of Blockchain-based access control systems for the healthcare system. In addition, for the healthcare system, we propose and implemented a decentralized role-based access control model based on Ethereum smart contract.